Optimalisasi Pembelajaran Matematika Menggunakan Aplikasi Prezi dan Permainan Ular Tangga - Chasanah, Chuswatun (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This research aims to optimize Mathematics Learning using the Prezi Application and Snakes and Ladders Game in Class 3 of SD Negeri 2 Sabranglor, Trucuk District, Klaten Regency. This research is qualitative research. The subjects of this research were 3rd grade students at SD Negeri 2 Sabranglor, Trucuk District, Klaten Regency. Research data was taken using test techniques. The research results were analyzed using interactive analysis techniques, namely data reduction, data presentation, and drawing conclusions. The research results show that there are five activities to optimize mathematics learning, namely preparing a learning implementation plan (RPP) using the NHT learning model with the Prezi application and the snakes and ladders game; create material with the Prezi application; make a game of snakes and ladders; carry out mathematics learning using lesson plans and learning media that have been prepared; and carrying out evaluations of students' mastery of the material after learning with the Prezi application and the snakes and ladders game. The use of the Prezi application and the snakes and ladders game had a good impact on grade 3 students at SD Negeri 2 Sabranglor, Trucuk District, Klaten Regency. This is indicated by the results/output as expected, namely the activity was carried out 100% with the results of a quite significant increase, namely from the original completion percentage of 25% increasing to 83% with an increase in the class average of 26.29 from the pre-test average of 53 .83 rose to 80.13.